SUBJECTIVE ASSESSMENTS OF RADIATION RISK ON THE TERRITORIES ADJACENT TO THE PLACES OF PEACEFUL NUCLEAR EXPLOSIONS - G. V. Arkhangelskaya; A. L. Vainberg; V. V. Gubernatorova; O. A. Daricheva; S. A. Zelentsova; I. A. Zykova; V. S. Repin; E. V. Khramtsov (Радиационная гигиена)
The article contains results of public opinion assessment of the radiation hazard due to consequences of two accidental peaceful nuclear explosions: Globus-1 in the Ivanovo region and Dnepr-1, Dnepr-2 in the Murmansk region. Results of query poll reveal that population knows about peaceful nuclear explosions that were done many years ago near their settlement. Radiation hazard and territory contamination due to these events is estimated by population as rather high. This public opinion is reflected in the information about consequences of peaceful nuclear explosions presented in the Internet and local printed mass media, especially due to consequences of accidental peaceful nuclear explosion Globus-1.